Marxist law theory and post-Soviet Russian philosophy (theory) of law - Сырых, Владимир (Hybris, 2018)
Russian legal theorists condemn Marxist law theory, without being truly familiar with it. The theory is criticized for dogmatism, for not being applicable to modern political and legal processes and phenomena and for providing justification of the mass terror taking place in the USSR in 1930s-40s. However, the above cannot be said to have any relation to the Marxist theory of law as such. What this criticism is really aimed at is its Soviet ver- sion based on the positivistic understanding of law as a set of rules of conduct established by the state. Whereas, the Marxist law theory views its subject matter as a form of economic relation, based on such principles as equality, free will, interdependence and universal validity of law. It is perhaps for that reason that the researchers who share a progressive, democratic view of law in- creasingly turn to Marxism when analyzing contemporary legal phenomena.